The Importance and Practice of Selection Breeding in Walnut - Şen Seyit Mehmet; Karadeniz Turan; Tekintaş Faik Ekmel; Güler Emrah (National and University Library of the Republic of Srpska, 2018)
In Turkey, the predominant method of walnut breeding is selection breeding which is the selection of elite genotypes as practiced worldwide. Due to this reason, the method of selecting elite genotypes with the desired agronomic characteristics is a short span and easily practicable. In countries, where the population of walnut is at low scale, hybridization practices are not attempted to acquire desired agronomic characteristics. The hybridization practices are time consuming to get the target genotypes. The walnut varieties improvement programs should include the priority issues such as: late leaf foliage, fruiting in lateral branches, shortening of the vegetation period, early maturity and harvesting, good fruit quality, high yield and resistance to diseases.
Keywords: productivity; walnut; breeding; Agriculture (General); selection; late foliage; S1-972; 2. Zero hunger; 15. Life on land